The Development of E-LKPD Based on Local Wisdom Subject of IPAS Subject of Chapter 5 Grade IV SDN 02 Sungai Rumbai - Melisa Anggrayni; Martiya Nurni Khairita; Fidiatul Ayu Riski (The Future of Education Journal, 2024)
This research aims to develop an Electronic Worksheet for Students based on Local Wisdom for the Social Sciences subject Chapter 5 in class IV. This e-LKPD aims to increase student activity, add interesting teaching materials, and improve learning outcomes so that learning objectives are achieved. This research is an R & D (Research and Development) research using the ADDIE research model. The research location was carried out at SDN 02 Sungai Rumbai, Sungai Rumbai District, Dharmasraya Regency. The research sample consisted of 18 students in class IV. The data collection instruments used were questionnaire and a 10-item multiple choice test, which had been tested for validity.The results of the research show that the effectiveness test of E-LKPD IPAS based on Local Wisdom in class IV at SDN 02 Sungai Rumbai was carried out in 3 meetings. At each meeting, students are required to complete the assignments and exercises contained in the E-LKPD. Then at the end of the meeting, students are given a test consisting of 10 multiple choice questions. After that, the author can describe the effectiveness of student learning, namely by measuring the level of achievement of the learning outcomes of class IV students at SDN 02 Sungai Rumbai. It is known that out of 18 students, 14 students were declared complete (reaching KKTP 70) with a percentage of 86% very effective. and 4 students were declared incomplete (did not reach KKTP 70) with a percentage of 5.5%.